Acoustic properties of selected liquids over the ultra- and hypersonic ranges - ŁABOWSKI, Mikołaj (Archives of Acoustics, 1980)
The paper presents the results of the investigation of the ultra- and hypersonic properties of some selected liquids. It also analyses the temperature variation of the ratio I_c/2I_MB in the fine structure of the Rayleigh line of scattered light. On the basis of the results of the experimental investigation it is shown that the following relaxation processes occur in the liquids investigated: rotational isomerism in n-hexane and iso-octane ; structural relaxation in isobutyric acid and vibrational relaxation in n-heptane. It has been observed that no acoustic dispersion occurs in nitroethane below a frequency of ~4 GHZ.